ChemInform Abstract: Highly Enantioselective Intramolecular 1, 3‐Dipolar Cycloaddition: A Route to Piperidino‐Pyrrolizidines. Issue 22 (15th May 2015) - Vidadala, Srinivasa Rao; Golz, Christopher; Strohmann, Carsten; Daniliuc, Constantin‐G.; Waldmann, Herbert
Abstract: A highly enantioselective synthesis of natural‐product‐inspired pyrrolidino‐piperidines by means of an intramolecular 1, 3‐dipolar cycloaddition with azomethine ylides is reported.